Kajian Perkembangan dan Lokasi Minimarket di Kawasan Tembalang - Marina, Syahira; Setyono, Jawoto Sih (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2012)
Tembalang area, located in the outskirt of Semarang city is experiencing the proliferation of modern convenient shops (minimarkets) dominated be Indomaret and Alfamart shops. Since 2001, 13 (thirteen) minimarkets have been established along the Jalan Bulusan to Jalan Ngesrep Timur corridor with the highest growth during the 2004â€2009 period. Most of the shops have been established by constructing on an empty land or residing a redesigned existing building. Consumer behavior analysis revealed that 39,9% consumer visits happens twice a week with 62,7% of them to buy daily consumer products. Proximity has been identified as the highest motivation to shop in these minimarkets, followed by variability of products. Locational analysis identified overlapping of service range of the minimarkets due to close proximity between each other. The minimarkets located in the Jalan Ngesrep Timur â€“ Jalan Prof. Sudarto corridor have the highest accessibility, while those located on Jalan Tirto Agung have the least. This study found oligopolistic competition among the two minimarkets.